2013
DOI: 10.1371/journal.pone.0068078
|View full text |Cite
|
Sign up to set email alerts
|

Early Phase of Plasticity-Related Gene Regulation and SRF Dependent Transcription in the Hippocampus

Abstract: Hippocampal organotypic cultures are a highly reliable in vitro model for studying neuroplasticity: in this paper, we analyze the early phase of the transcriptional response induced by a 20 µM gabazine treatment (GabT), a GABA-Ar antagonist, by using Affymetrix oligonucleotide microarray, RT-PCR based time-course and chromatin-immuno-precipitation. The transcriptome profiling revealed that the pool of genes up-regulated by GabT, besides being strongly related to the regulation of growth and synaptic transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 196 publications
3
5
0
Order By: Relevance
“…The SRF-mediated regulation of these transcription factors seems to be rather common and conserved regardless of different cell types. Indeed, the involvement of SRF inferred by CIDER in the regulation of this cluster is consistent with the results of a similar study on hippocampal rat cells 16 , where a time-series cluster analysis of a set of 33 genes identified a subset of genes, including FOS , EGR1 , EGR2 , EGR4 , DUSP1 and NR4A1 , enriched for the SRF binding motif. Chromatin Immunoprecipitation (ChIP) experiments confirmed that SRF was binding to the promoters of FOS , EGR1 , EGR2 and NR4A1 16 .…”
Section: Resultssupporting
confidence: 90%
“…The SRF-mediated regulation of these transcription factors seems to be rather common and conserved regardless of different cell types. Indeed, the involvement of SRF inferred by CIDER in the regulation of this cluster is consistent with the results of a similar study on hippocampal rat cells 16 , where a time-series cluster analysis of a set of 33 genes identified a subset of genes, including FOS , EGR1 , EGR2 , EGR4 , DUSP1 and NR4A1 , enriched for the SRF binding motif. Chromatin Immunoprecipitation (ChIP) experiments confirmed that SRF was binding to the promoters of FOS , EGR1 , EGR2 and NR4A1 16 .…”
Section: Resultssupporting
confidence: 90%
“…The effects of bicuculline suggest a role for enhanced excitatory transmission in the regulation of CCN1 mRNA levels. Similar results were obtained in organotypic hippocampal slices (Iacono et al, 2013 ). In vivo , CCN1 mRNA level increases with decreases in excitatory transmission that are caused by N -methyl-D-aspartate receptor inhibition (Ito et al, 2007 ).…”
Section: Expression and Functions Of Ccn Family Members In The Nervousupporting
confidence: 86%
“…To confirm the microarray data, reverse transcriptase polymerase chain reaction (RT-PCR), an accepted method for validating microarray results in the neuroscience field [ 56 59 ], was applied to randomly up- and down-regulated genes using 3`-UTR specific gene primers ( S3 Table ). Briefly, total RNA samples were first DNase-treated with RNase-free DNase (QIAGEN, Maryland).…”
Section: Methodsmentioning
confidence: 99%